Implementation of the Love-Based Curriculum (KBC) in the Madrasah Diniyah Program to Strengthen Students’ Religious Competence - H. Heriyanto; Itsnaini Muslimati Alwi (Manunggal Halim Jaya, 2026)
This study aims to describe the implementation of the Love-Based Curriculum (KBC) in the Madrasah Diniyah program, analyze the strategies employed by teachers in its application, and examine its impact on students’ religious competence at MTs Muhammadiyah Kemuning. This research uses a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. Data analysis was conducted through systematic processes of data reduction, data display, and conclusion drawing. The results of the study indicate that the implementation of KBC is carried out through approaches of compassion, role modeling, and consistent habituation of worship practices. Teachers apply several strategies, including building emotional closeness with students, creating an enjoyable learning atmosphere, and providing continuous spiritual reinforcement. The impact of the implementation of KBC can be seen in the improvement of students’ ability to read the Qur’an, mastery of prayer memorization, and the development of more consistent religious behavior. In addition, there is an increase in students’ discipline, responsibility, and social awareness in their daily lives. These findings demonstrate that KBC is effective as a learning approach in strengthening students’ religious competence within the Madrasah Diniyah environment. This study provides practical implications for the development of compassion-based learning models in Islamic education. However, this research is limited to a specific contextual setting; therefore, further studies are needed to test the generalizability of these findings across different contexts and educational levels more comprehensively. Future research is also recommended to employ mixed-methods approaches, thereby strengthening the results, making them quantitatively measurable, and enabling more objective comparisons regarding the effectiveness of KBC implementation in various Islamic educational settings.